2018
DOI: 10.1021/acsomega.7b01834
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Bonding Interactions of m-Chlorotoluene with 1-Alkanol Analyzed by Thermodynamic, Fourier Transform Infrared Spectroscopy, Density Functional Theory, and Natural Bond Orbital

Abstract: Fourier transform infrared spectroscopy (FT-IR) has been employed to obtain information about the nature of interactions in the liquid solutions of pure solvents and their mixtures of m- chlorotoluene (MCT) with 1-alkanol systems at different mole fractions. Furthermore, densities (ρ) and speeds of sound ( u ) of binary mixtures of MCT with a set of five 1-alkanols, namely, 1-propanol, 1-butanol, 1-pentanol, 1-hexanol, and 1-heptanol, were measured as a function of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 60 publications
0
8
0
Order By: Relevance
“…The experimental values of density and speed of sound of samples were determined using Rudolph Research Analytical Digital Densitometer (DDM-2911 model) and single crystal ultrasonic interferometer (model F-05) from Mittal Enterprises, New Delhi, India. In our earlier articles, , ultrapure water was used to calibrate the instruments, and we described the details of measurements and calibration of the instruments. The uncertainties were estimated for density and speed of sound measurements within 0.008 g·cm –3 and 2.8 m·s –1 , respectively.…”
Section: Methodsmentioning
confidence: 99%
“…The experimental values of density and speed of sound of samples were determined using Rudolph Research Analytical Digital Densitometer (DDM-2911 model) and single crystal ultrasonic interferometer (model F-05) from Mittal Enterprises, New Delhi, India. In our earlier articles, , ultrapure water was used to calibrate the instruments, and we described the details of measurements and calibration of the instruments. The uncertainties were estimated for density and speed of sound measurements within 0.008 g·cm –3 and 2.8 m·s –1 , respectively.…”
Section: Methodsmentioning
confidence: 99%
“…But when two kinds of organic compound are copresent either in the liquid or the solid phase, their intermolecular interaction via dipolar forces and hydrogen bonding ought to be considered. [82][83][84][85][86] The intermolecular interaction may cause unexpected deviations of the molecular vibrational spectra. 82,[84][85][86] Our IR spectral analysis of a mixture of AA and potassium lactate on KBr shows the presence of an additional band at 1690 cm −1 together with the upward shift of a 1593 cm −1 band to 1600 cm −1 and the shift of other bands (Fig.…”
Section: Papermentioning
confidence: 99%
“…[82][83][84][85][86] The intermolecular interaction may cause unexpected deviations of the molecular vibrational spectra. 82,[84][85][86] Our IR spectral analysis of a mixture of AA and potassium lactate on KBr shows the presence of an additional band at 1690 cm −1 together with the upward shift of a 1593 cm −1 band to 1600 cm −1 and the shift of other bands (Fig. S17 †).…”
Section: Papermentioning
confidence: 99%
“…With the approaching electrophile behaviour one of the Hatom of a loop got substituted and the product additionally holds its balance and fragment in nature. [7][8][9][10] Herein, several studies [11,12] have been reported to understand the interaction of 1-alkanols with other organic hydrocarbon liquids via utilizing the U analysis. [12] Further, ternary blends with 1-alkanols as one component are indispensable for the industries to prevent the development of azeotropes in extractive distillation.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9][10] Herein, several studies [11,12] have been reported to understand the interaction of 1-alkanols with other organic hydrocarbon liquids via utilizing the U analysis. [12] Further, ternary blends with 1-alkanols as one component are indispensable for the industries to prevent the development of azeotropes in extractive distillation. The earlier reported literatures show that these studies with higher primary alcohols are not at all available.…”
Section: Introductionmentioning
confidence: 99%